Analysis of Needs in The Development of Website-Based E-Modules for Self-Study - Nina Ikhwati Wahidah; Niki Tri Sakung; Ike Festiana; Willy Artanika Rikarda; Iskandar .; Agus Komarudin (Peneliti.net, 2021)
The goal of this series of articles is to examine the necessity for developing Islamic religious education e-modules in higher education. The phase of needs analysis is the most crucial in the development of models, materials, or learning mediums. When instructional designers conduct research before formulating plans, developing materials, or putting them into action, they save a lot of money, time, and effort. Rowntree's research and development process has been modified with Hannafin and pack models in this study. For the purpose of analyzing the writer's needs utilizing the survey approach. This study used a sample of 50 students. Students demand online learning material, according to the results of the needs analysis. Students prefer learning that includes simulations and hands-on experience. Expected content includes a detailed discussion of the topic matter. Today's media include power point presentations and the utilization of educational materials. The existence of a computer laboratory is heavily supported by technology in the faculty of science and technology. It is required to build e-module learning materials based on the results of the needs analysis. Because e-module learning materials may help students learn independently and can be accessed anywhere and at any time, they were chosen. This needs analysis is part of the e-module creation research for Higher Education courses in Islamic Religious Education.